How change leadership affects change adaptability? Investigating the moderated mediation effect of cognitive resistance and change efficacy - Muhammad Kashif Imran; Syed Muhammad Javed Iqbal (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
Drawing on the social cognitive theory, this research examines the relationship between organizational change leadership and change adaptability with mediating effect of change efficacy and moderating role of cognitive resistance. A longitudinal research design with a three-waved data collection procedure was followed to obtain responses from 246 employees working in services sector organizations operating in the province of Punjab, Pakistan. The obtained data were analyzed through Process Macro technique introduced by Hayes (2017) using SPSS 25. The results demonstrated that change leadership has a significant positive impact on change adaptability and change efficacy partially mediated the stated relationship. Further, cognitive resistance to change moderated the mediated relationship between change leadership and change adaptability through change efficacy. This research introduced an innovative model to initiate and implement an organizational change initiative with the help of organizational change leadership. Further, findings also highlighted the importance of developing change efficacy and managing cognitive resistance to change to increase the success ratio of any organizational change process. This research offered implications for the practice side to deploy the services of change leaders to manage the affairs related to organizational change. Furthermore, the key task of the change leaders is to increase the change efficacy and reduce the cognitive resistance to implement an organizational change successfully. This research adopted a novel approach to link a specialized branch of leadership (i.e., change leadership) with change adaptability by addressing the cognitive patterns of employees during change.
Keywords: 330; organizational change leadership; change efficacy; cognitive resistance tochange; change adaptability; social cognitive theory